The powerful intellectuality of black people: trajectory of Professor Dr. Maria Zelma de Araújo Madeira – an inspiration (PerCursos, 2024)
The interview shows the successful trajectory of Maria Zelma de Araújo Madeira, a black woman, born into a family with few economic resources, in the interior of the state of Piauí.  Racism and sexism, expressions that are so naturalized but must be faced on a daily basis, have permeated his history, but have also become central objects of contestation in his experience in defending human rights in the state of Ceará, where he resides and currently works as Secretary State of Racial Equality. It is also worth highlighting that he graduated in Social Work and has a doctorate in Sociology. She is a professor of the Social Service Course and the Academic Master's in Social Service, Work and Social Issues (MASS), at the Universidade Estadual do Ceará (UECE).